Implementation of strategic human resource management in SAARP project of edotco Bangladesh co. LTD - Ahamed, Marzia (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.